Pengaruh Faktor Kebudayaan, Sosial, Pribadi dan Psikologi terhadap Perilaku Pembelian - Nila Desanda Dara Ayu; Tantri Widiastuti (Jurnal Ilmiah Aset, 2011)
The purpose of this study was to determine the influence of cultural factors, social factors, personal factors, and psychological factors on consumer behavior in the purchase of liquid soap at Toko Sami Untung Pasar Mrican Semarang. The population in this research was all consumers who bought soap liquid in Toko Sami Untung Pasar Mrican Semarang by the number of samples used 100 respondents. The sampling technique used in this study was convenience sampling and the analysis tool used wasmultiple linear regression. The results showed that based on a partial test of the hypothesis with the t test results obtained for X1 = 13.525; X2 = 4.394 and X3 = 2.397 and t table 1.985, so it lied in refused Ho, it means that there was a significant effect between cultural factors, social factors, factors personal, and psychological factors on consumer behavior in the purchase of liquid soap at Toko Sami Untung Pasar Mrican Semarang. The coefficient of determination of the four independent variables of 79.6% means that the variation of the four independent variables in explaining consumer behavior and 20.4% is explained by other variables that are not mentioned in this study, such as pricing, quality service and product quality.